PELATIHAN PENGOLAHAN TEPUNG AMPAS KELAPA MENJADI BISKUIT DI DESA ADAT PENGLIPURAN, KABUPATEN BANGLI - I W. R. Widarta; I K. Suter; N M. Yusa; A.A. I.S. Wiadnyani; NN. Puspa wati; K. A. Nocianitri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2013)
Penglipuran village located on Bangli sub-district in Bangli regency. Coconut is one of agricultural commoditiesin this village. Rural community in Penglipuran village are inexperienced how to make cookies by coconut-byproduct. The aim of these activities was to introduce cookies production by coconut-by product to increase theadded.value The Community Service was carried out by 2 methods, namely: first, information and discussionwith rural community about cookies. Second, cookies production training. There are 20 partisipant in this activity,including delegation of female farmer groups. They have given positif response for these valuable activity.